Analisis Pelayanan Lapak Asik Dalam Sistem Klaim Jaminanan Hari Tua Dibadan Penyelanggara Jaminan Sosial (BPJS) Ketenagakerjaan Cabang Kota Padang Sidempuan - Manik, Risnainun Wahyuli; Arif, Muhammad; Harahap, Muhammad Ikhsan (Universitas Labuhanbatu, 2024)
The implementation of the Old Age Insurance (JHT) claim system at the Padangsidempuan Branch Employment BPJS has several obstacles, one of which is the lack of understanding of participants regarding the JHT claim system which results in ineffective utilization of the claim system provided through Lapak Asik. by BPJS Ketenagakerjaan, Padang Sidempuan City Branch. The purpose of this study is to see how the description of the implementation of JHT claims at the Padangsidempuan Branch Employment BPJS. This research method uses descriptive qualitative primary and secondary data. Data collection techniques that have been carried out by way of interviews and documentation studies. The results of the study show that the implementation of the Old Age Security (JHT) claim system at the Padangsidempuan City Branch of Employment BPJS is not in accordance with existing regulations. This is due to the fact that many participants make JHT claims but do not attachrequirements such as a certificate of termination of employment, so that participants experience failure in making their JHT claims. The utilization of the JHT claim system at Bukalapak is less effective. This is because there are still many participants who make claims directly to the Branch Office. In fact, through Asik Stalls it is more efficient for the participants' time.